GOLD INVESTMENT OPPORTUNITIES THROUGH GOLD INSTALLMENT PRODUCTS OF BANK SYARIAH INDONESIA KCP PROBOLINGGO - Lutfi Riadi; fitrotin indah saro (Universitas Nurul Jadid, 2024)
Investment involves allocating a portion of one's wealth withthe expectation of future profits. Among various investment options, gold has gained popularity due to its perceived safety and profitability. One option for investing in gold is through BSI's gold installment plan. This financing product enables customers to acquire gold in the form of bullion by paying in installments, structured under murabaha contracts. To initiate this process, customers make an initial down payment of 20%, with the remaining 80% payable in installments. This studyaims to explore potential investment opportunities available through BSI's gold installment financing at the KCP Probolinggo office. To achieve this, a qualitative descriptive approach was employed through field research. The findings indicate that opportunities for investment in gold installment products are trending positively. Among the various advantages, gold investments often prove to be more profitable than cash, as they are less susceptible to inflation.Furthermore, gold is easy to buy and sell, the margins offered are competitive, and gold prices have historically shown an upward trend each year.